Morphological Investigation Of Precipitated Calcium Carbonate (PCC) Characteristics With The Presence Of Additives During Synthesis - Rohazam, Nurul Zulaikha (Universiti Sains Malaysia, 2017)
The research was conducted in order to investigate the crystal morphology of precipitated calcium carbonate (PCC) characteristics during the synthesis with the presence of additives. The controlling variables such as concentration of calcium hydroxide (milk of lime) and flow rate of carbon dioxide gas influences the particle size and polymorph of crystal of precipitated calcium carbonate. In this research, two types of additives are being used to distinguish based on the precipitated calcium carbonate characteristics. An additive changes the surface of crystal materials and particle size. It was found that slaked lime in the presence of EDTA changing the rhombohedral calcite crystal into spherical calcite or prismatic calcite. PCC widely being used in many applications because of the stability of PCC compare others, the pure whiteness of PCC and the compatibility of PCC mixed with others. Increases flow rate of carbon dioxide gas into the calcium hydroxide solution affected the size particle of suspension of PCC. 20ml/min and 10ml/min were being chosen to study the effect of rate flow of carbon dioxide gas towards the polymorph. The increases concentration of “milk of lime” will change the shape crystal suspension of PCC. 0.9M and 0.5M concentration of calcium hydroxide being used in this research to study how concentration of “milk of lime” plays a role in influences of polymorph of PCC. Thus, all the parameters need to consider before begins synthesis of calcium carbonate.